FUNGSI DAN KATEGORI FRASA ADJEKTIVAL PADA KALIMAT SEDERHANA DALAM NOVEL SENSE AND SENSIBILITY KARYA JANE AUSTEN - UTAMI, TYAS HILDA; PAKASI, JENNY H.; LOTULUNG, DONALD R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis study is entitled â€œFunction and Category of Adjectival Phrase in Simple Sentence in the Novel Sense and Sensibility by Jane Austenâ€. The aim of this study is an attempt to identify, classify, and analyze the adjectival phrase in simple sentence found in the novel in terms of its functions and categories. The method used in this research is a descriptive method. There are three steps in finish this study, first is preparation, the writer reads concept from the book related to syntactic structure and browses journals related to adjectival phrase in the internet; second is data collection, the data were taken from the Sense and Sensibility novel by Jane Austen in order to identify and classify them based on the Aarts & Aarts (1982) theory; the third step is the writer analyzing the data using tree diagram. The result of this study shows that adjectival phrase in a sentence can be divided into function as a subject attribute and function as an object attribute. In the simple sentence structure, the functions found externally are subject, predicate, and adverbial. Internally, the functions found are predicator and complement which realized by subject attribute and object attribute. The categories found in the simple sentence are noun phrase, verb phrase, and adjectival phrase. Internally, only the structures of the adjectival phrase which is analyzed. The internal structure of adjectival phrase found are adjectival which realized by category adjective. The writer found one hundred and twenty six adjectival phrases as subject attribute including seven head functions, sixty four premodifiers, twenty four postmodifiers, twenty four pre and postmodifiers, and seven discontinuous modifiers; and twenty two adjectival phrases as object attribute including thirteen premodifiers, four postmodifiers, three pre and postmodifiers and two discontinuous modifiers. The head function of adjectival phrase as object attribute is not identified.Â Keywords: Function, Category, Adjectival Phrase, Sense and Sensibility